Tetrahymena thermophila Predation Enhances Environmental Adaptation of the Carp Pathogenic Strain Aeromonas hydrophila NJ-35 - Liu, Jin; Dong, Yuhao; Wang, Nannan; Li, Shougang; Yang, Yuanyuan; Wang, Yao; Awan, Furqan; Lu, Chengping; Liu, Yongjie (Frontiers in Cellular and Infection Microbiology, 2018)
Persistence of Aeromonas hydrophila in aquatic environments is the principle cause of fish hemorrhagic septicemia. Protistan predation has been considered to be a strong driving force for the evolution of bacterial defense strategies. In this study, we investigated the adaptive traits of A. hydrophila NJ-35, a carp pathogenic strain, in response to Tetrahymena thermophila predation. After subculturing with Tetrahymena, over 70% of A. hydrophila colonies were small colony variants (SCVs). The SCVs displayed enhanced biofilm formation, adhesion, fitness, and resistance to bacteriophage infection and oxidative stress as compared to the non-Tetrahymena-exposed strains. In contrast, the SCVs exhibited decreased intracellular bacterial number in RAW264.7 macrophages and were highly attenuated for virulence in zebrafish. Considering the outer membrane proteins (OMPs) are directly involved in bacterial interaction with the external surroundings, we investigated the roles of OMPs in the antipredator fitness behaviors of A. hydrophila. A total of 38 differentially expressed proteins were identified in the SCVs by quantitative proteomics. Among them, three lipoproteins including SurA, Slp and LpoB, and a serine/threonine protein kinase (Stpk) were evidenced to be associated with environmental adaptation of the SCVs. Also, the three lipoproteins were involved in attenuated virulence of SCVs through the proinflammatory immune response mediated by TLR2. This study provides an important contribution to the understanding of the defensive traits of A. hydrophila against protistan predators.